Post-Welfare Lawyering: Clinical Legal Education and a New Poverty Law Agenda - Juliet M. Brodie (Washington University Journal of Law & Policy, 2006)
Ours is the “post-welfare” era, and it is ripe with opportunities for poverty lawyers to shape a new poverty law agenda. This era is characterized by the millions of former welfare recipients who entered the wage-labor force, and by a new public dialogue about post-welfare poverty. Journalists, social scientists, and policymakers have been watching these “welfare leavers,” assessing their labor market participation, their “success,” and their economic well-being. Together, these observers and actors have created a new academic, political, and cultural terrain on which American poverty is debated and constructed—one where “the working poor” has replaced “the welfare recipient” as the trope of American poverty. Poverty lawyers must account for this new social category and, I argue, should take advantage of the current historical moment to expand justice for these workers and others in post-welfare poverty.
Keywords: Legal assistance to the poor; Clinical legal education; Public welfare; Working poor; Wages; Poverty; Social justice; Welfare reform; United States